Capturing Early Childhood Educators’ Learning Process in the New Normal: A Case Study of a Group Childcare Center in British Columbia, Canada - Villamera, Inocenta; Chavez, Judith (JPAIR Institutional Research, 2022)
Childhood educators are adjusting as they transition from the global pandemic to the new normal. This qualitative study explored the learning processes facilitated by teachers for children in a group childcare center in British Columbia, Canada, during the new normal. The case study identified six teachers who were purposefully identified based on the following criteria: being licensed childhood educators, teaching in the facility, and showing a willingness to participate in the study. The twenty young children were likewise chosen considering these conditions: they are enrolled in the facility, aged three to four, and their parents gave their written consent. In-depth interviews, classroom observations, photographs, and field notes were utilized. Trustworthiness was also observed in the study. Findings reveal three emerging themes: engaging children in deliberate play-based activities streamlining classroom management, and challenging and rewarding learning. The study concludes that the teachers’ learning process is characterized by high learner engagement in deliberate play-based activities. The facilitators of learning have to streamline their classroom management through creative scaffolding, collaboration, and modifications in their teaching and pacing. Facilitating learning is a confluence of challenges, job fulfillment, and positive impact. Thus, further investigation may be conducted to verify the findings in other childcare centers in British Columbia, Canada.
Keywords: Education; childhood educators; learning process; new normal; child care center; qualitative; Canada